Intrinsic Magnetism and Field‐Driven Spin Alignment in NiI2 Revealed by X‐ray Magnetic Spectroscopy - Arnold, Ethan L.; Heppell, Emily; Basnet, Rabindra; Zhang, Binshuo; Liu, Jieyi; Herrero‐Martín, Javier; Guillemard, Charles; Guo, Yanfeng; Hu, Jin; Backes, Dirk; van der Laan, Gerrit; Hesjedal, Thorsten (Physica status solidi. PSS-RRL. Rapid research letters, 2025)
This study investigates the intrinsic magnetism and field‐driven spin alignment in NiI2 using X‐ray absorption spectroscopy and X‐ray magnetic circular dichroism (XMCD). NiI2, a van der Waals material, exhibits helimagnetic and type‐II multiferroic behavior. This study reveals robust XMCD signals across paramagnetic, antiferromagnetic, and helimagnetic phases under applied out‐of‐plane fields up to 6 T, while no net moment emerges at zero field. Atomic multiplet calculations confirm a covalent Ni 3d ground state with a significantly reduced spin moment. The results establish the intrinsic nature of NiI2's magnetism and clarify its field‐driven spin alignment mechanism. This comprehensive spectroscopic characterization lays the foundation for future applications of NiI2 in advanced spintronic and multiferroic devices, despite challenges posed by its low transition temperature in the monolayer limit. Future research should focus on enhancing its critical temperature through doping, strain engineering, or heterostructure fabrication. The 2D van der Waals multiferroic NiI2 exhibits type‐II multiferroicity down to the monolayer limit, but its spin alignment mechanism has remained unclear. Arnold et al. made a major step in this direction by using X‐ray magnetic spectroscopy to reveal field‐driven spin alignment from a strongly covalent Ni 3d ground state.